Partial hydrolyzed protein as an alternative stabilizer for peanut (Arachis hypogaea) butter - Thongkong S; Rakairyatham K; Tangjaidee P; Unban K; Klangpetch W; Phimolsiripol Y; Rachtanapun P; Rawdkuen S; Singh J; Kaur L; Issara U; Kingwascharapong P; et al. (Elsevier Ltd, 2025)
Peanut protein hydrolysates with varying degrees of hydrolysis (DH) were prepared by using Alcalase and Flavourzyme. The enzymatic hydrolysis highly influenced a transformation of protein secondary structures, particularly from β-sheet to β-turn structures (11–21 %). The DH impacted functional properties and anti-free radicals' activity of peanut protein hydrolysates. Flavourzyme-derived protein hydrolysate (FPH) with DH5% had the maximum potential as an emulsifier (54.50 ± 0.71 %, p < 0.05). The effectiveness of protein hydrolysates in preventing the oil separation and enhancing the oxidative stability of peanut butter was dependent on the type of enzyme and DH. The inclusion of partial hydrolyzed protein (DH5%) produced by the Alcalase (APH) substantially decreased the occurrence of oil separation; whereas FPH with DH5% significantly retarded increment of PV, TBARs, CD in peanut butter during the storage period (p < 0.05). This study indicated the possible use of partial hydrolyzed proteins as a stabilizer in peanut butter by slowing lipid oxidation and increasing oil entrapment.
Keywords: Protein hydrolysate; Emulsifier; Peanut butter; Lipid oxidation; Antioxidant peptides